Communication Strategy for New Public Transport System (Case Study: PT Mass Rapid Transit (MRT) Jakarta Communication Strategy) - Maulidiyanti, M (KnE Social Sciences, 2018)
This research discusses communication strategy role in the process of building a positive image and public trust toward the new public transportation system in Jakarta, Mass Rapid Transit (MRT) Jakarta. This article examined how communication strategy plays a strategical role during significant project phase. According to the experience, differentiated communication tactics during different phases of project can have an important role on public level of acceptance. Communication strategy is very important because the MRT Jakarta is the first MRT system in Indonesia. It is carried out by the government companies that are called PT MRT Jakarta. It is fully funded by the government through Japanese loans. As a Public Project using the state budget, MRT has always been in a public spotlight and vulnerable to be a hot issue. Moreover, people are required to be patient waiting for the MRT through the construction phase that would always bring the impact and changes for the community (traffic jam along the corridor, land acquisition, etc.). From the service, MRT Jakarta is also expected to be able to encourage people shift from private vehicles to public transport. To achieve this, the company needs a comprehensive communication strategy since the preconstruction & construction phase until the operation period. So this research is attempting to explore MRT Jakarta Company communication strategy to achieve those goals. Through qualitative descriptive method, research aims to find if the Corporate Communication Division implements the effective strategy based on the theory or not. This method systematically describes the communication strategy formulated by MRT Jakarta Company. The research used interview method to collect the data. From this research, we know that PT MRT Jakarta builds key messages, chooses the campaign program, chooses the media tools and how the PR measures for the success of the program. Keywords: public relations, communication strategy, Mass Rapid Transit (MRT), transportation, descriptive